3D bioprinting of photocrosslinkable hydrogel constructs. Issue 48 (21st July 2015) - Pereira, Rúben F.; Bártolo, Paulo J.; Pantani, Prof. Roberto; Turng, Prof. Lih‐Sheng
ABSTRACT Three‐dimensional (3D) bioprinting comprises a group of biofabrication technologies for the additive manufacturing of 3D constructs by precisely printing biocompatible materials, cells and biochemicals in predesigned spatial positions. These technologies have been successfully applied to fabricate biodegradable 3D constructs with intricate architectures and heterogeneous composition, assuming a pivotal role in the field of tissue engineering. However, the full implementation of bioprinting strongly depends on the development of novel biomaterials exhibiting fast crosslinking schemes and appropriate printability, cell‐compatibility and biomechanical properties. Photocrosslinkable hydrogels are attractive materials for bioprinting as they provide fast polymerization under cell‐compatible conditions and exceptional spatiotemporal control over the gelation process. Photopolymerization can also be performed during the bioprinting to promote the instantaneous formation of hydrogel with high well‐defined architecture and structural stability. In this review paper, we summarize the most recent developments on bioprinting of photocrosslinkable biodegradable hydrogels for tissue engineering, focusing on the chemical modification strategies and the combination of photocrosslinking reactions with other gelation modalities. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42458.